Simulation and Evaluation Hydrogen-rich Syngas Production from Palm Kernell Shell Through Gasification - Kasmiarno, Laksmi Dewi; Nurufazzah, Arifatin (Politeknik Negeri Jakarta, 2025)
The increasing global demand for energy, coupled with the depletion of fossil fuel reserves, has prompted the urgent need for alternative and sustainable energy sources. Biomass, particularly palm oil waste such as palm kernel shell (PKS) presents as an alternative solution due to its abundance, high calorific value, and low moisture content. This study investigates the production of syngas from PKS through gasification using Aspen PlusTM process simulation software. The simulation is divided into pre-treatment, gasification, and separation stages, employing R-Stoic, R-Yield, and R-Gibbs reactor blocks to model drying, decomposition, and thermodynamic equilibrium, respectively. Two gasifying agents, steam and air, were evaluated under varying temperature conditions and equivalence ratio (ER) ranging from 0.19 to 0.27. The results indicate that both temperature and ER significantly influence syngas composition, particularly the production of H2 and CO, while higher ER values tend to reduce carbon efficiency. Steam gasification produced higher hydrogen yields compared to air. Simulation outputs showed strong agreement with experimental data, validating the model’s accuracy. This study demonstrates the potential of PKS gasification for renewable energy generation and highlights the effectiveness of process simulation for system design and optimization prior to industrial implementation.